Ethnic-racial Disparity and Mortality Due to Covid-19: Case Study of two Medium-sized Cities - Gariboti, Diuster Franceschi; Silva Júnior, Flavio Manoel Rodrigues (Sociedade & Natureza, 2022)
Ethnic-racial disparity is a disturbing adversity that is present in the current context of Brazilian society. During the New Coronavirus pandemic, different countries around the world pointed out the relationship between this and other socioeconomic vulnerabilities and mortality from the virus. This research aimed to analyze and substantiate how an ethnic-racial disparity was present during the COVID-19 pandemic, contextualizing the problem from the analysis of two medium-sized cities located in Rio Grande do Sul: Rio Grande, RS and Pelotas, RS. The article was based on the hypothetical-deductive approach method, with the use of the bibliographic research technique together with the case study, in which the general mortality rates of the population and the mortality stratified among whites, blacks and browns were estimated, based on data from the Civil Registry of Deaths in the cities mentioned. The results obtained in the present study show higher mortality rates among blacks than among whites (an increase of 36% in Rio Grande and 46% in Pelotas), similarly to results obtained in other studies that investigated Brazilian metropolises. In the meantime, the findings of this study expand the issue of ethnic-racial disparity in the context of the COVID-19 pandemic beyond the large Brazilian metropolises and highlight a structural problem in medium-sized cities.